The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346773
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cy-5 siRNA signal in the intra-vital multi-photon microscopy images

Abstract: Transgenic mice with Tie2- green fluorescent protein (GFP) are used as a model to study the kinetic distribution of the Cy5-siRNA delivered by lipid nanoparticles (LNP) into the liver. After the mouse is injected with the LNP, it undergoes a procedure of intra-vital multi-photon microscopy imaging over a period of two hours, during which the process for the nanoparticle to diffuse into the hepatocytes from the vasculature system is monitored. Since the images are obtained in-vivo, the quantification of Cy5 kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…[261] These studies highlighted a strategy to manipulate cellular biodistribution of NPs via altering surface coating and charge of the nanomaterials. Single-cell hepatic distributions of PMMA NPs, [262] liposomes, [263] and silicone NPs [264] were studied by IVM. In particular, van der Vos et al have used data obtained from IVM to construct computational models of NP biodistribution in an effort to minimize the hepatic uptake and maximize the tumor accumulation.…”
Section: Imaging Pk and Biodistribution Of Materials In Clearance Organsmentioning
confidence: 99%
“…[261] These studies highlighted a strategy to manipulate cellular biodistribution of NPs via altering surface coating and charge of the nanomaterials. Single-cell hepatic distributions of PMMA NPs, [262] liposomes, [263] and silicone NPs [264] were studied by IVM. In particular, van der Vos et al have used data obtained from IVM to construct computational models of NP biodistribution in an effort to minimize the hepatic uptake and maximize the tumor accumulation.…”
Section: Imaging Pk and Biodistribution Of Materials In Clearance Organsmentioning
confidence: 99%
“…Although many studies have reported the organ‐level distribution of NPs, very few have addressed their disposition in organs at the cellular level . The uptake, distribution and excretion of fluorescent or fluorescent labelled NPs can be investigated using TPEF imaging at the single cell resolution . Polymeric NPs with high bond repetition rate are highly suitable for CARS imaging because the CARS signal scales quadratically with the bond concentration .…”
Section: Pharmacokinetic Imaging In the Livermentioning
confidence: 99%
“…The analysis of the diffusion of Cy5-siRNA into the hepatocytes was done by computation of the percentage signal strength in the region of interest over time. 78 Another study reported a significant uptake of positively charged, but not negatively charged moieties. Negatively charged nanoparticles were found to be taken up by Kupffer cells as shown by intravital imaging.…”
Section: Nanoparticlesmentioning
confidence: 99%